1989
DOI: 10.1021/bi00434a046
|View full text |Cite
|
Sign up to set email alerts
|

Aminophospholipid translocase of human erythrocytes: phospholipid substrate specificity and effect of cholesterol

Abstract: The outside-inside translocation rate and transmembrane equilibrium distribution, at 37 degrees C, of 16 different amphiphilic spin-labeled phospholipids have been determined in human erythrocytes. The transmembrane distribution was assessed by bovine serum albumin extraction of the spin-labels present in the outer monolayer. Within 15 min, more than 90% of the phosphatidylserine analogue was found in the inner monolayer; the equilibrium distribution of phosphatidylethanolamine spin-label was approximately 85-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
148
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(170 citation statements)
references
References 31 publications
21
148
1
Order By: Relevance
“…On the other hand, PE allowed the protein to express some activity. This remarkably specific lipid specificity expressed by the Mg2+-ATPase parallels the substrate specificity of the aminophospholipid translocase [2,16]: the enzyme transports PS and PE, but the apparent affinity of PS is one order of magnitude higher than that of PE. Besides, lyso PS is not a good substrate and is transported very inefficiently, and PC is not recognized at all by the carrier.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the other hand, PE allowed the protein to express some activity. This remarkably specific lipid specificity expressed by the Mg2+-ATPase parallels the substrate specificity of the aminophospholipid translocase [2,16]: the enzyme transports PS and PE, but the apparent affinity of PS is one order of magnitude higher than that of PE. Besides, lyso PS is not a good substrate and is transported very inefficiently, and PC is not recognized at all by the carrier.…”
Section: Discussionmentioning
confidence: 78%
“…The human erythrocyte membrane and other plasma membranes contain an aminophospholipid translocase which actively transports phosphatidylserine (PS) and phosphatidylethanolamine (PE) from the outer to the inner monolayer [1,2]. This transport requires the hydrolysis of cytosolic ATP [1,3,4], the presence of magnesium [5] and is inhibited by vanadate [1,5]; it is therefore a vanadate sensitive Mg-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, all SL-LPC were extracted from liposomes and bound to BSA. It has been previously shown that BSA can extract those analogs from the exposed outer leaflet but not from the inner leaflet (35).…”
Section: Interaction Of Sl-lpc With Intact and Bromelain-treated Virumentioning
confidence: 99%
“…Myeloperoxidase released from activated neutrophils may also add to oxidant challenge in SCA, through production of hypochlorous acid (HOCl) from hydrogen peroxide (Vissers et al , 1994; Mutze et al , 2003; Zhang et al , 2013). Thiol oxidation has also been associated with both inhibition of the flippase and stimulation of the scramblase (Morrot et al , 1989; Connor & Schroit, 1990; Devaux & Zachowski, 1994; Martin & Jesty, 1995; de Jong & Kuypers, 2006). In addition, the normal antioxidant capacity of the red cell is compromised in SCA patients, with low availability of antioxidant enzymes, reduced levels of glutathione (GSH) and also of non‐enzymatic antioxidants, such as vitamins C and E (Silva et al , 2013).…”
mentioning
confidence: 99%